SHAYX MUHAMMAD SODIQ MUHAMMAD YUSUF ILMIY MEROSINI O‘RGANISHNING NAZARIY ASOSLARI - Alimov Muhammadali Mulloyevich, (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
Shaykh Muhammad Sadiq Muhammad Yusuf is recognized not only in Uzbekistan but also throughout the Islamic world as a prominent religious scholar, renowned Qur’anic exegete, and jurist. His scholarly heritage includes deep studies on the sciences of the Qur’an and Hadith, addressing doctrinal, jurisprudential, and ethical issues. Shaykh’s works not only contribute to the development of the theoretical foundations of religious sciences but also serve as a key resource for developing new approaches that align with the needs of modern society.